Kajian Filsafat Ilmu terhadap Pertambangan Batubara sebagai Upaya Meningkatkan Kesejahteraan Rakyat Indonesia - Irsan Irsan; Meria Utama (Fakultas Hukum Universitas Islam Indonesia, 2016)
The major issue in this research is about the study on the general philosophy (ontology, epistemology and axiology) towards the use of natural resource of coal mining as an effort to improve the Indonesian people welfare. This is a normative research in which the research approach used the approach of philosophy of laws examining the legal values embedded in the law and regulation related to the use of natural resource of coal mining in Indonesia. the result of the research showed that first, in the study of ontology, coal mining has contributed to the national economy that is supposed to be run in harmony with the Article 33 sentence (3) and (4) of Constitution 1945. Reflection now is the governance of state is more dominant in its use; thus, it needs a new balance in the form of national management policy. Second, in the study of epistemology, there is a need to use the principle of sustainable development in the coal mining with people economic system and even distribution; and third, in axiology, there is a need of the direct and indirect use in improving the welfare of Indonesian people.